A novel protein domain in an ancestral splicing factor drove the evolution of neural microexons. - Torres-Méndez, A.; Bonnal, S.; Marquez, Y.; Roth, J.; Iglesias, M.; Permanyer, J.; Almudí, I.; O'Hanlon, D.; Guitart, T.; Soller, M.; Gingras, A.C.; Gebauer, F.; et al. (Nature ecology & evolution, 2019)
The mechanisms by which entire programmes of gene regulation emerged during evolution are poorly understood. Neuronal microexons represent the most conserved class of alternative splicing in vertebrates, and are critical for proper brain development and function. Here, we discover neural microexon programmes in non-vertebrate species and trace their origin to bilaterian ancestors through the emergence of a previously uncharacterized 'enhancer of microexons' (eMIC) protein domain. The eMIC domain originated as an alternative, neural-enriched splice isoform of the pan-eukaryotic Srrm2/SRm300 splicing factor gene, and subsequently became fixed in the vertebrate and neuronal-specific splicing regulator Srrm4/nSR100 and its paralogue Srrm3. Remarkably, the eMIC domain is necessary and sufficient for microexon splicing, and functions by interacting with the earliest components required for exon recognition. The emergence of a novel domain with restricted expression in the nervous system thus resulted in the evolution of splicing programmes that qualitatively expanded the neuronal molecular complexity in bilaterians.